A channel-structured Eu-based metal–organic framework with a zwitterionic ligand for selectively sensing Fe3+ ions. Issue 38 (12th June 2018) - Huang, Yong-Qing; Chen, Huai-Ying; Wang, Yang; Ren, Yong-He; Li, Zong-Ge; Li, Lu-Chao; Wang, Yan
Abstract : A channel-structured Eu-based metal–organic framework with a zwitterionic ligand may serve as a sensor for selectively detecting Fe 3+ ions. Abstract : A novel Eu-based MOF [Eu(IMS1)2 ]Cl·4H2 O (1 ) was successfully constructed based on a semi-rigid zwitterionic 1, 3-bis(4-carboxylbenzyl)-imidazolium (IMS1) ligand, featuring a 3-fold interpenetrating dia net structure with a point symbol of 6 6 and charged permanent micropores. Considering its excellent luminescent property as well as thermal and chemical stability, complex1 was explored as a potential sensor for detecting Fe 3+ ions. The results show that complex1 has a high sensitivity and selectivity for Fe 3+ based on a 'turn-off' effect, for which the electrostatic interaction between Fe 3+ ions and the inner surface of the micropores may play a critical role. The fluorescence quenching mechanism reveals that dynamic quenching and competitive adsorption between Fe 3+ and1 lead to the quenching effect of1 .